The Use of Cefiderocol in Gram-Negative Bacterial Infections at International Medical Center, Jeddah, Saudi Arabia - Reham Kaki; Amjad Taj; Sultan Bagaaifar (MDPI AG, 2024)
Background/Objectives: The necessity for ground-breaking treatments for Gram-negative infections is evident. The World Health Organization, the Infectious Diseases Society of America, and the European Commission have highlighted the critical insufficiency of efficient antibiotics, urging pharmaceutical businesses to manufacture new antibiotics. Therefore, developing new antibiotics with broad efficacy against Gram-negative pathogens is essential. Thus, this research aimed to evaluate the safety and effectiveness of cefiderocol in treating multidrug-resistant Gram-negative bacterial infections at the International Medical Center (IMC), Jeddah, Saudi Arabia. Methods: A retrospective analysis was conducted on patients treated from January 2021 to February 2023. Thirteen case groups treated with cefiderocol were compared to twenty control groups treated with other antibiotics. Results: The results indicated no statistically significant differences in ICU stay, comorbidity indices, or mortality rates between the two groups. Cefiderocol showed high clinical and microbiological cure rates, despite the severity of the patients' conditions. Carbapenem-resistant Klebsiella pneumoniae and difficult-to-treat resistance Pseudomonas aeruginosa were the most prevalent pathogens in the case and control group, respectively. Two patients treated with cefiderocol developed Clostridioides difficile infection, emphasizing the need for close monitoring of potential adverse effects. Conclusions: The results of this study support cefiderocol as a viable alternative for managing serious infections instigated by multidrug-resistant Gram-negative bacteria.